2015
DOI: 10.3345/kjp.2015.58.3.84
|View full text |Cite
|
Sign up to set email alerts
|

Update of genetic susceptibility in patients with Kawasaki disease

Abstract: Kawasaki disease (KD) is an acute systemic vasculitis that predominantly affects children, and can result in coronary artery lesions (CAL). A patient with KD who is resistant to treatment with intravenous immunoglobulin (IVIG) has a higher risk of developing CAL. Incomplete KD has increased in prevalence in recent years, and is another risk factor for the development of CAL. Although the pathogenesis of KD remains unclear, there has been increasing evidence for the role of genetic susceptibility to the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…The ITPKC gene codes for one of the three isoenzymes of inositol 1,4,5-triphosphate 3-kinase that is involved in the Ca 2+ /nuclear factors of activated T- cells (NFAT) signaling pathway in T cells [29]. It functions as a negative regulator of T cell activation [29].…”
Section: Etiopathogenesismentioning
confidence: 99%
See 4 more Smart Citations
“…The ITPKC gene codes for one of the three isoenzymes of inositol 1,4,5-triphosphate 3-kinase that is involved in the Ca 2+ /nuclear factors of activated T- cells (NFAT) signaling pathway in T cells [29]. It functions as a negative regulator of T cell activation [29].…”
Section: Etiopathogenesismentioning
confidence: 99%
“…It functions as a negative regulator of T cell activation [29]. Onouchi et al in 2008 reported that single nucleotide polymorphisms (SNPs) in ITPKC on chromosome 19q13.2 were associated with susceptibility to KD and risk of coronary artery abnormalities in Japanese and American children (rs28493229) [30].…”
Section: Etiopathogenesismentioning
confidence: 99%
See 3 more Smart Citations